NLRP3, the inflammasome and COVID-19 infection - O'Neill, Luke (My University, 2023)
Severe coronavirus disease 2019 (COVID-19) is characterized by respiratory failure, shock or multiorgan dysfunction, often accompanied by systemic hyperinflammation and dysregulated cytokine release. These features are linked to the intense and rapid stimulation of the innate immune response. The NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome is a central player in inflammatory macrophage activation which via caspase-1 activation leads to the release of the mature forms of the proinflammatory cytokines interleukin (IL)-1β and IL-18, and via cleavage of Gasdermin D pyroptosis, an inflammatory form of cell death. Here, we discuss the role of NLRP3 activation in COVID-19 and clinical trials currently underway to target NLRP3 to treat severe COVID-19.
PUBLISHED
Keywords: Severe coronavirus disease 2019 (COVID-19); respiratory failure; systemic hyperinflammation